Intracultivar selection for seed quality of soybeans in an ultra-low-density selection model (Honeycomb Selection Designs) - Karla Bianca de Almeida Lopes; Antônio Eduardo Pípolo; José Henrique Bizzarri Bazzo; Claudemir Zucareli (Acta Scientiarum: Agronomy, 2020)
Selecting genotypes that combine high productivity with high seed quality is a challenge. The exploration of intracultivar genetic variation is an alternative to significantly increase the annual genetic gain and maximize the selection efficiency for both characteristics. The present study aimed to identify intracultivar variation to improve the seed quality of soybean genotypes derived from the commercial cultivar BRS 284, selected using the HSD (Honeycomb Selection Designs) model. Soybean genotypes selected for two years from two environments with contrasting edaphoclimatic characteristics, according to the principles of the HSD selection model, were cultivated under competition by using the experimental model in randomized blocks with four replicates and evaluated regarding the productivity and physiological quality of seeds. The results showed that genotype 284-3 presented a greater mass of 100 seeds, germination, vigour after accelerated ageing test, seedling emergence and emergence speed index than the other genotypes in both environments, with no significant difference in the standard cultivar regarding seed yield. The HSD method was an efficient selection method to identify intracultivar variation to improve cultivar performance.